HEART AND LUNG FAILURE, TRANSPLANTOLOGYA functional assessment of patients two years after lung transplantation in Poland - Jastrzębski, Dariusz T.; Gumola, Anna; Wojarski, Jacek; Żegleń, Sławomir; Ochman, Marek; Czyżewski, Damian; Ziora, Dariusz; Zembala, Marian; Kozielski, Jerzy (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
The aim of the study was to assess the long-term results of lung transplantation (LT) in Poland two years after the procedure. Material and methods : The study included patients who underwent LT between December 2004 and December 2009 in the Silesian Center for Heart Diseases in Zabrze. Various lung functions (forced vital capacity – FVC; forced expiratory volume in 1 second – FEV1), the quality of life (SF-36 questionnaire), the level of perceived dyspnea (Medical Research Council – MRC; basic dyspnea index – BDI), and the patient’s mobility (the 6-minute walking test – 6MWT) were assessed before and approximately 24 months after LT. Among 35 patients who underwent LT, 20 patients were referred to our study (mean age: 46.6 ± 9.03 years). Results: After LT, a statistically significant increase was observed in the distance achieved in the 6MWT (323.8 vs. 505.8 m), FVC (1.64 vs. 2.88 L), and FEV1 (1.37 vs. 2.09 L). An improvement in perceived dyspnea in MRC and BDI questionnaires was observed in patients with chronic obstructive pulmonary disease (COPD) after LT. The assessment of the quality of life, excluding perceived pain, showed the most significant improvement in the physical cumulative score (PCS; 25 vs. 45 points), especially in patients with idiopathic pulmonary fibrosis. Conclusions: Lung transplantation in Poland, in patients who live longer than 2 years after the procedure, significantly improves the mobility, lung function, perceived dyspnea, and the quality of life.